2010
DOI: 10.1161/circulationaha.110.960864
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letters Regarding Article, “Television Viewing Time and Mortality: The Australian Diabetes, Obesity and Lifestyle Study (AusDiab)”

Abstract: We thank Drs Ding, Mekary, and Katz for their interest in our recent findings showing a positive association between television viewing time and mortality. 1 Drs Ding and Mekary helpfully bring to our attention the relevance of their isotemporal substitution model to our findings. Consistent with their perspective, we acknowledge that the basic partition model applied in our analyses has limitations with respect to not being able to account for total activity time. As a potential explanation of the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
226
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(266 citation statements)
references
References 4 publications
13
226
1
7
Order By: Relevance
“…Our all-cause mortality results are in agreement with a large study of Canadian adults who were followed up for 12 years, where the all-cause mortality HR for the highest category of nonrecreational (work, school, housework) daily sitting time ("almost all the time") was 1.54 (26). Another study among Ͼ8,000 Australian adults reported a very similar all-cause mortality HR (1.46) for Ն4 h of TV watching compared with the Ͻ2 h/day reference group (23). Both studies were also robust for adjustments or stratifications by sex, physical activity level, smoking, and BMI.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our all-cause mortality results are in agreement with a large study of Canadian adults who were followed up for 12 years, where the all-cause mortality HR for the highest category of nonrecreational (work, school, housework) daily sitting time ("almost all the time") was 1.54 (26). Another study among Ͼ8,000 Australian adults reported a very similar all-cause mortality HR (1.46) for Ն4 h of TV watching compared with the Ͻ2 h/day reference group (23). Both studies were also robust for adjustments or stratifications by sex, physical activity level, smoking, and BMI.…”
Section: Discussionmentioning
confidence: 95%
“…Although we found no evidence of a dose-response relationship, our analysis suggests that a threshold of Ն2 h/day of screen time might be linked to an increased risk for a CVD event. The Australian study (23) found that daily TV viewing times in excess of 4 h/day (but not 2 to 4 h/day) were associated with CVD death risk. We speculate that this disagreement occurs because our exposure variable was more inclusive than TV alone that was used in the Australian study and because our CVD outcome included nonfatal as well as fatal events.…”
Section: Discussionmentioning
confidence: 99%
“…Increased time spent in sedentary behaviors has been associated with colorectal, endometrial, ovarian, and prostate cancer risk [79] as well as insulin resistance, elevated CRP [80] and all-cause mortality [81]. These associations are generally independent of time spent engaging in moderate-vigorous intensity physical activity [82].…”
Section: Limitationsmentioning
confidence: 99%
“…In addition to the health benefits of being highly active, health risks are related to sedentary behaviours (Dunstan et al 2010;Hamilton et al 2007;Healy et al 2008). Sedentary behaviour or inactivity refers to activities that do not increase energy expenditure substantially above the resting level and includes activities such as sleeping, sitting, lying down, and watching television, and other forms of screen-based entertainment (Pate et al 2008).…”
Section: Introductionmentioning
confidence: 99%